Antibiotic resistance and molecular typing of clinical Staphylococcus aureus isolates from Malaysian military hospital - Shakrin, NikNoorul Shakira Mohamed; Junaidi, NorSyaza Syahirah Amat; Huri, MohammadFahmi Daman; Kamarudin, AhmadZakwan; Desa, MohdNasir Mohd; Yunus, WanMohd Zin Wan (Wolters Kluwer - Medknow Publications and Media, 2023)
Objective: To determine the antibiotic resistance profile (ARP) of Staphylococcus (S.) aureus isolates and molecular typing of the methicillin-resistant S. aureus (MRSA) isolates from Tuanku Mizan Armed Forces Hospital (TMAFH), Kuala Lumpur. Methods: The ARP and presence of the pvl gene were determined for 209 S. aureus isolates from clinical specimens. Of these, 123 were methicillin-susceptible S. aureus (MSSA) isolates and 86 were MRSA isolates. All MRSA isolates were characterized using SCCmec typing and spa typing. Descriptive analysis was performed to compare the demographic data with the phenotypic and genotypic variables of the S. aureus isolates. Results: No vancomycin-intermediate and-resistant S. aureus (VISA and VRSA, respectively) were detected among the study isolates. The MSSA isolates showed low resistance rates to all tested antibiotics, were commonly invasive (28/42, 66.7%), and mostly harboured pvl (35/42, 83.3%). Meanwhile, MRSA isolates showed high resistance to penicillin (86/86, 100%), ampicillin (86/86, 100%), sulbactam/ampicillin (86/86, 100%), cefuroxime (81/86, 94.19%), cefoperazone (76/86, 88.37%), azithromycin (56/86, 65.12%), and erythromycin (54/86, 62.79%). The majority of MRSA isolates were of SCCmec type IVh (65/86, 75.58%), spa type t032 (55/85, 63.95%), and grouped into spaCC-T022 (66/85, 77.65%). The t032 type was found to be associated with resistance traits to azithromycin and erythromycin (P<0.05). We also found several spa types that are typically associated with hospital-, community-, and livestock-Associated MRSA co-existing in our MRSA population. Conclusions: This study reflected the consistent absence of VISA and VRSA and corroborated the clonal shifting of MRSA isolates in the Malaysian MRSA isolates.